Do I Belong in the Profession? The Cost of Fitting In as a Preservice Teacher With a Passion for Social Justice. (September 2019) - McKay, Loraine; Manning, Heather
Preservice teachers enter university with a range of personally held beliefs related to inclusive education and themselves as educators. This article reports on one case study from a larger qualitative research project. The study examined a preservice teacher's perceptions of herself as an inclusive educator as she approached the final year of her undergraduate degree. Data included a metaphorical representation of being an inclusive educator, and two semi-structured interviews held 6 months apart. The use of collage and a structured written response completed the data set. Evelein and Korthagen's model of core reflection and Voice-Centred Relational Method were used to analyze the data. Analysis exposed the dissonance between the layers that separate the preservice teacher's core qualities and the environment. Data are presented using I-poems and discussed using the emerging themes. The consequences for her emerging identity as an inclusive educator and sense of belonging in the profession are discussed.